An ultra-high performance liquid chromatography method to determine the skin penetration of an octyl methoxycinnamate-loaded liquid crystalline system - Prado, A. H. [UNESP]; Borges, M. C. [UNESP]; Eloy, J. O. [UNESP]; Peccinini, R. G. [UNESP]; Chorilli, M. [UNESP] (My University, 2017)
Cutaneous penetration is a critical factor in the use of sunscreen, as the compounds should not reach systemic circulation in order to avoid the induction of toxicity. The evaluation of the skin penetration and permeation of the UVB filter octyl methoxycinnamate (OMC) is essential for the development of a successful sunscreen formulation. Liquid-crystalline systems are innovative and potential carriers of OMC, which possess several advantages, including controlled release and protection of the filter from degradation. In this study, a new and effective method was developed using ultra-high performance liquid chromatography (UPLC) with ultraviolet detection (UV) for the quantitative analysis of penetration of OMC-loaded liquid crystalline systems into the skin. The following parameters were assessed in the method: selectivity, linearity, precision, accuracy, robustness, limit of detection (LOD), and limit of quantification (LOQ). The analytical curve was linear in the range from 0.25 to 250 μg.m-1, precise, with a standard deviation of 0.05-1.24%, with an accuracy in the range from 96.72 to 105.52%, and robust, with adequate values for the LOD and LOQ of 0.1 and 0.25 μg.mL-1, respectively. The method was successfully used to determine the in vitro skin permeation of OMC-loaded liquid crystalline systems. The results of the in vitro tests on Franz cells showed low cutaneous permeation and high retention of the OMC, particularly in the stratum corneum, owing to its high lipophilicity, which is desirable for a sunscreen formulation.